ADAPTATION STRATEGIES AND PERCEPTIONS OF FARMERS TOWARD CLIMATE CHANGE IMPACTS ON REPONG DAMAR (Shorea javanica) IN PAHMUNGAN AND GUNUNG, LAMPUNG PROVINCE - Yuli Rosianty; Delfy Lensari, S.Hut, M.Si; Purwani Purwani (Sylva Jurnal Ilmu-ilmu Kehutanan, 2025)
Climate change is a significant issue that poses a threat to humans, especially in Indonesia. The impacts on Damar trees due to climate change include reduced sap production, increased water content during the rainy season, and decreased size and quality of Damar sap during the dry season, necessitating community perception and adaptation in responding to climate change. Data collection was conducted in two villages: Pahmungan Village, Pesisir Tengah District, and Gunung Kemala Village, Way Krui District, Pesisir Barat Regency, Lampung Province. The research used quantitative and qualitative methods. Data analysis was conducted using a Likert scale and descriptive methods. The results of this study are the knowledge of Repong Damar farmers for Gunung Kemala village (81%) and Pahmungan village (89%) with the category of strongly agree, the perception of the attitude of Repong Damar farmers for Gunung Kemala village (83%) and Pahmungan village (87%) with the category of strongly agree, the perception of Repong Damar farmers' skills for Gunung Kemala village (82%) and Pahmungan village (88%) with the category of strongly agree, and the adaptation carried out by Repong Damar farmers, namely by cultivating pepat/damar tree holes, and looking for side jobs.